Implications of Laboratory Tests in Disease Grading and Death Risk Stratification of COVID-19: A Retrospective Study in Wuhan, China - Bai, Yang; Wang, Enxin; Zhao, Shoujie; Li, Jing; Zhu, Yejing; Zhang, Yongchao; Cao, Liang; Liu, Haitao; Dong, Yushu; Wang, Fang; Liang, Guobiao; Liu, Lei (Frontiers in Medicine, 2021)
Background: Although laboratory tests have become an indispensable part in clinical practice, its application in severity classification and death risk-stratification of COVID-19 remains unvalidated. This study aims to explore the significance of laboratory tests in the management of COVID-19. Methods: In 3342 hospitalized patients with COVID-19, those of mild or moderate subtype were categorized into non-severe group, while those of severe or critical subtype categorized into severe group. Initial laboratory data were analyzed and compared according to disease severity and outcome. Diagnostic models for severe group were generated on risk factors identified by logistic regression and receiver operating characteristic (ROC) analyses. Cox regression and ROC analyses on risk factors were utilized to construct prognostic models. Results: In identification of patients in severe group, while age, neutrophil-to-lymphocyte ratio, α-hydroxybutyrate dehydrogenase were identified as independent predictors, the value of combination of them appears modest (area under the curve; AUC = 0.694). Further ROC analyses indicated that among patients in severe group, laboratory indices had favorable value in identifying patients of critical subtype rather than severe subtype. For death outcome, IL-6, co-existing cerebrovascular disease, prothrombin time activity, and urea nitrogen were independent risk factors. An IL-6 single-parameter model was finalized for distinguishing between fatal and recovered individuals (AUC = 0.953). Finally, a modified death risk-stratification strategy based on clinical severity and IL-6 levels enables more identification of non-survivors in patients with non-critical disease. Conclusions: Laboratory screening provides a useful tool for COVID-19 management in identifying patients with critical condition and stratifying risk levels of death.